ANALISIS PENGGUNAAN APLIKASI MAXIM MENGGUNAKAN MODEL UTAUT2 (STUDI KASUS: MAHASISWA PENDIDIKAN KOMPUTER FKIP UNIVERSITAS MULAWARMAN) (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital transportation has transformed students’ mobility patterns in supporting academic activities. Maxim, as one of the online transportation applications, is widely used by students of the Computer Education Study Program, Faculty of Teacher Training and Education, Mulawarman University. However, the factors influencing the intention and usage behavior still require further analysis. This study aims to examine the effect of variables in the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model on Behavioral Intention and Use Behavior in using the Maxim application. This research employed a quantitative approach with a survey method involving 75 students selected using the Slovin formula (10% error rate) and purposive sampling technique. Data were analyzed using multiple linear regression with IBM SPSS version 22. The results indicate that partially Effort Expectancy (t = -3.662; sig. = 0.000), Hedonic Motivation (t = 3.435; sig. = 0.000), Price Value (t = 3.817; sig. = 0.000), and Habit (t = 4.980; sig. = 0.000) significantly influence Behavioral Intention, while Performance Expectancy does not (t = 0.489; sig. = 0.626). Behavioral Intention significantly affects Use Behavior (t = 6.416; sig. = 0.000), whereas Habit does not (t = 0.936; sig. = 0.352). Simultaneously, all independent variables significantly influence the dependent variables (sig. = 0.000). The coefficient of determination (R²) shows a strong explanatory power. These findings suggest that ease of use, enjoyment, price value, and habit influence intention, while usage behavior is primarily driven by intention.